Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, Sanksi Pajak, Tarif Pajak dan Kewajiban Moral terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Samsat Kabupaten Tegal - Hargiyarto, Ibnu Malik; Witono, Banu (LPPM Institut Nasional Laa Roiba Bogor, 2024)
ABTRACT This research is quantitative research. Quantitative research is research based on the philosophy of positivism to study certain populations or samples, data collection using research instruments, quantitative or statistical data analysis which aims to test predetermined hypotheses. This quantitative research aims to test the influence of existing variables, namely to test the influence of tax knowledge, taxpayer awareness, tax sanctions, tax rates and moral obligations on motor vehicle taxpayer compliance. The population in this study is motor vehicle taxpayers. registered at the Tegal Regency SAMSAT office. The sample in this study were motor vehicle taxpayers with motorbikes and cars registered at the Tegal Regency SAMSAT office. The sampling technique used is accidental sampling, that is, anyone who accidentally or accidentally meets the researcher can be used as a sample (Sugiyono, 2017). The data used in this research is primary data. According to Narimawati (2008) quoted by Rahadian & Herawati (2018) primary data is data obtained from original sources or first hand. The data collection method in this research is by distributing questionnaires to respondents, namely motor vehicle taxpayers in Tegal Regency. These data were analyzed using SPSS software. Keywords: Tax Knowledge, Taxpayer Awareness, Tax Sanctions, Tax Rates, Moral Obligations